2020
DOI: 10.5365/wpsar.2020.11.3.003
|View full text |Cite
|
Sign up to set email alerts
|

Intensified research on tuberculosis in the Western Pacific Region: a bibliometric analysis, 2000–2019

Abstract: “Intensified TB research and innovation” is one of the three pillars of the End TB Strategy. To assess achievements and gaps in tuberculosis (TB) research productivity in countries and areas of the Western Pacific Region quantitatively, a bibliometric analysis was carried out by examining trends in the numbers of publications on TB indexed in PubMed between 2000 and 2019 and by comparing them with trends in publications on other selected major infectious diseases for the same period. The number of publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Our search strategy retrieved relevant studies of pulmonary TB conducted primarily in high-burden countries; however, studies focusing on clinical pharmacy services for TB in other countries were limited. We found this in line with the trend of increasing TB research in high-burden countries with more context-specific research to meet its own national strategic plan goals toward TB elimination, where fundamental and epidemiology research is mainly conducted (Cazabon et al, 2017;World Health Organization, 2017;Nafade et al, 2018;Morishita et al, 2020), making studies on clinical pharmacy services in TB relatively uncommon. A review also highlighted this by stating that clinical pharmacy services primarily target specific medical conditions, but TB was not mentioned (Rotta et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our search strategy retrieved relevant studies of pulmonary TB conducted primarily in high-burden countries; however, studies focusing on clinical pharmacy services for TB in other countries were limited. We found this in line with the trend of increasing TB research in high-burden countries with more context-specific research to meet its own national strategic plan goals toward TB elimination, where fundamental and epidemiology research is mainly conducted (Cazabon et al, 2017;World Health Organization, 2017;Nafade et al, 2018;Morishita et al, 2020), making studies on clinical pharmacy services in TB relatively uncommon. A review also highlighted this by stating that clinical pharmacy services primarily target specific medical conditions, but TB was not mentioned (Rotta et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…In the studies we reviewed, clinical pharmacy services were given as a supplementary service, focusing on its utilization to enhance an existing TB care program, supported by multiple relevant patientrelated data sources to provide the service appropriately (World Health Organization, 2017;World Health Organization, 2019c;Mahmoud, 2019). This practical type of study falls into an operational research category to maximize the effectiveness and efficiency of interventions that can contribute to achieving the desired TB outcome (Kumar et al, 2020;Morishita et al, 2020). However, the absence of sound randomized studies of clinical pharmacy services as part of existing TB care indicated that accurate assessments of the effect of clinical pharmacy services within TB care are difficult.…”
Section: Discussionmentioning
confidence: 99%
“…While TB research outputs in the Region as a whole increased by 8.8% annually between 2000 and 2018, there are still major knowledge gaps in some countries such as the Lao People's Democratic Republic and Mongolia. 10 Operational research can generate context-specific evidence to inform decision-making and improvements to national programmes, and thus requires adequate funding.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Nafade et al ., in 2018 analyzed global trends of research before 2016, and the analysis by Igwaran and Edoamodu only targeted Africa; another by Morishita et al ., targeted the Western Pacific. [ 19 20 21 ] A study with a global aspect was, therefore, necessary. This study aimed to perform a bibliometric analysis of TB research from 2011 to 2020 to discover research performance and trends from a global perspective.…”
Section: Introductionmentioning
confidence: 99%